Security Risk Analysis and Countermeasure Research for Computing Power Network - WANG Xinnan; CHENG Qiyue; LU Jun (天地一体化信息网络)
With the development of the digital economy era, emerging technologies have brought about a rapid growth of data, the demand for computing power and network in all aspect of social life has increased dramatically. In the face of this demand, computing force network has emerged. However, new technologies and new network architectures also bring new security risks, the original security measures can no longer meet the demand for computing power security. Due to the widely distributed and massive multi-source computing power and networks have broken the traditional security domains, the computing force networks have been seriously threatened in terms of data security, network security and privacy security. The latest research results and technologies related to computing force network security were sorted out from the perspectives of computing force network architecture security, computing force network data security, network resource security, computing resource security, network resource management security and computing service security. It analyzed the causes of the security risks and system threats faced by computing force networks and give countermeasure suggestions to strengthen the security of computing force networks, aimed to establish a comprehensive and multi-layered security protection system for computing power network sand resist system risks from data, network, resources, services, and other aspects.